TUBERCULOSE MILIAR: RELATO DE CASO - KLIDZIO, BREENDA; JESUS, LAIANE CRISTINE STRADA DE; REBELLATO, ISABELA TEIXEIRA; HICKMANN, LUIS FELIPE PEDROLO; MANICA, PEDRO HENRIQUE GONÇALVES; PARISE, LUÍGGI SALLA; TISOTT, GIOVANA CASARIN; KORSACK, PAULA LUZA (Salão do Conhecimento, 2025)
TUBERCULOSE MILIAR: RELATO DE CASO